1987
DOI: 10.1017/s0021859600079521
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance of field beans (Vicia faba L.) in relation to interactions between inflorescences at different nodes

Abstract: Competitive and regulatory effects of defined inflorescences on the development of other inflorescences and subsequent yield performance of field beans (Viciafaba. L.) were investigated. Genotypes differing greatly in yield performance (two inbred lines and the F t hybrid produced from the two inbred lines) were used in both field and pot experiments. Yield was manipulated by the removal of defined inflorescences at various times and positions.In comparison with untreated control plants the removal of up to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Experiments in which light, leaf area or the number of developing fruits are varied (McAlister & Krober, 1958;Sheldrake, 1979;Aufhammer, Gotz & Peter, 1987) indicate that the supply of photosynthate may be critical at these stages. Peet et al (1977) found for example that the yield of dry bean was correlated with the rate of photosynthesis at the time of pod set for eight out of nine cultivars tested.…”
Section: From Flower To Fruitmentioning
confidence: 99%
“…Experiments in which light, leaf area or the number of developing fruits are varied (McAlister & Krober, 1958;Sheldrake, 1979;Aufhammer, Gotz & Peter, 1987) indicate that the supply of photosynthate may be critical at these stages. Peet et al (1977) found for example that the yield of dry bean was correlated with the rate of photosynthesis at the time of pod set for eight out of nine cultivars tested.…”
Section: From Flower To Fruitmentioning
confidence: 99%
“…T M T R o n u r T i D M (White et al 1984), the release of abscission-inducing Dybing 1980) and the control of photosynthate grain legumes results in realizations of reproductive competition between reproductive and vegetative sink potential ranging from 10 to 30% (Sinha 1977) sinks (Clifford 1981;Aufhammer et al 1987). This and is a critical physiological trait determining paper reports a series of experiments in which a range harvestable yield (Hardwick 1988).…”
Section: Effects Of Growth Regulators On Reproductive Abscissionmentioning
confidence: 99%
“…Mit der Entfernung der zwei proximalen Bliiten an den Infloreszenzen der Nodien 3-6 (ROWLAND et al 1984, AuFHAMMER et al 1987, weisen in die gleiche Richtung. Zusammengenommen heifit dies: Konkurrenz innerhalb und zwischen vegetativen und generativen Organen um Assimilate verhindert eine vermehrte Nutzung angebotenen Speicherpotentials.…”
Section: Effekte Der Behandlungunclassified